Psychometric properties of dexterity questionnaire-24 in Iranian chronic stroke survivors. Issue 3 (3rd April 2022) - Dehmiyani, Arian; Taghizadeh, Ghorban; Azad, Akram; Goudarzi, Sepideh; Jamali, Shamsi; Hejazi Shirmand, Mahnaz; Rostami, Siavash; Mehdizadeh, Maryam
ABSTRACT: Introduction: Dexterity is one of the most critical upper extremity functions that may be impaired in chronic stroke survivors. This study aimed to investigate the psychometric properties of DextQ-24 in Iranian chronic stroke survivors. Method: A total of 123 people with chronic stroke were included in the study. Internal consistency and test-retest reliability were assessed through Cronbach's alpha and Interclass Correlation (ICC), respectively. Dimensionality was performed by Exploratory Factor Analysis. In addition, to assess the convergent validity of DextQ-24, Box and Block Test, Motor Activity Log Questionnaire, ABILHAND Questionnaire, and Purdue Pegboard Test were used. Discriminant validity of DextQ-24 was measured between different stages of recovery (Brunnstrom stage). Acceptability was calculated by ceiling and floor effect. Results: Cronbach's alpha and ICC were 0.92 and 0.91, respectively. The 24 items of this questionnaire were classified into six components. Further, a moderate to strong correlation between the total score of DextQ-24 with other tools | r = 0.41-0.84 | was obtained. The results of discriminant validity approved the ability of the total score of DextQ-24 to separate different stages of recovery. The results also reported that this questionnaire did not have a significant ceiling and floor effect. Conclusion: The results of our study showed that the Persian DextQ-24 has high reliability and a good convergent and discriminant validity in people with chronic stroke for dexterity measurement as a PROM questionnaire.